Antimicrobial activity of jambu mawar [Syzygium jambos (L.) Alston] leaf extract against foodborne pathogens and spoilage microorganisms - S. K., Ali (UPM Press, 2022)
The present work evaluated the antimicrobial potential of the ethanolic extract of jambu mawar [Syzygium jambos (L.) Alston] leaves against various foodborne pathogens and spoilage microorganisms via the disc diffusion assay (DDS) and the time-kill curve assay. These microorganisms included bacteria (Klebsiella pneumoniae ATCC13773, Listeria monocytogenes ATCC19112, Proteus mirabilis ATCC21100, Pseudomonas aeruginosa ATCC9027, Staphylococcus aureus ATCC29737, and Vibrio parahaemolyticus ATCC17802), yeasts (Candida albicans ATCC10231, C. krusei ATCC32196, C. glabrata ATCC2001, and C. parapsilosis ATCC22019), and moulds (Aspergillus fumigatus ATCC26430, A. niger ATCC9029, Rhizopus oligosporus ATCC22959, and R. oryzae ATCC22580). The inhibition zone of DDA ranged from 7.00 ± 0.23 to 10.25 ± 0.29 mm. The minimum inhibitory concentration (MIC) and minimum bactericidal/fungicidal (MBC/MFC) of the ethanolic leaf extract were obtained at the concentrations of 0.01 to 2.50 and 0.01 to 5.00 mg/mL, respectively. The time-kill curve assay showed that except for P. mirabilis, other microorganisms were completely killed at MIC concentrations ranging from 0.5 to 4× MIC. In comparison, P. mirabilis showed a growth reduction of > 3 log10 CFU/mL for 4 h. Meanwhile, the conidial germination of A. fumigatus was fully inhibited at 0.5× MIC. Though not fully inhibited, the ethanolic leaf extract significantly reduced the conidial germination of A. niger, R. oryzae, and R. oligosporus to 7.0, 7.0, and 11.0%, respectively. Overall, the ethanolic leaf extract of S. jambos exhibited antimicrobial activity against foodborne pathogens and spoilage microorganisms.